2022
DOI: 10.53730/ijhs.v6ns2.7264
|View full text |Cite
|
Sign up to set email alerts
|

Variations in origin of inferior pancreaticoduodenal artery

Abstract: Coeliac trunk and Superior Mesenteric arteries are very much susceptible to variations and were described by Tandler in 1904. Abdominal aorta branches are classified as single double or visceral parietal. Double visceral branches are middle suprarenal, renal and testicular arteries and single visceral branches are coeliac trunk, superior mesenteric and inferior mesenteric arteries. Materials and Methods:  After obtaining ethical committee approval, we observed the origin, course and branching pattern of pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Kotapalli et al observed an additional IPDA which originated from 2nd jejunal branch of SMA (7). In our study too, the accessory IPDA was present but it was seen to be originating from SMA.…”
Section: Splenic Arterysupporting
confidence: 58%
See 1 more Smart Citation
“…Kotapalli et al observed an additional IPDA which originated from 2nd jejunal branch of SMA (7). In our study too, the accessory IPDA was present but it was seen to be originating from SMA.…”
Section: Splenic Arterysupporting
confidence: 58%
“…Pro ciency in the arterial branches and their variant anatomy is utmost required to avert complications like ischemia, necrosis of duodenum and head of pancreas during surgical interventions. (5)(6)(7) Expertise in the variant anatomy will enhance the readiness for sudden modi cations which may be required in arterial embolization procedures intraoperatively.…”
Section: Introductionmentioning
confidence: 99%